Nile Tilapia Fish Skin–Based Wound Dressing Improves Pain and Treatment-Related Costs of Superficial Partial-Thickness Burns: A Phase III Randomized Controlled Trial. Issue 5 (May 2021) - Lima Júnior, Edmar Maciel; de Moraes Filho, Manoel Odorico; Costa, Bruno Almeida; Fechine, Francisco Vagnaldo; Vale, Mariana Lima; Diógenes, Ana Kely de Loyola; Neves, Kelly Rose Tavares; Uchôa, Alex Marques do Nascimento; Soares, Maria Flaviane Araújo do Nascimento; de Moraes, Maria Elisabete Amaral
Abstract : Background: In a phase II study comparing Nile tilapia fish skin to silver sulfadiazine cream for outpatient management of superficial partial-thickness burns, the fish skin decreased reepithelialization time (average reduction, 1.43 days), dressing changes (average reduction, 3.72 dressings), and visual analogue scale pain scores. The present study aimed to further evaluate Nile tilapia fish skin efficacy for superficial partial-thickness burns. Unlike silver sulfadiazine cream, the fish skin has good adherence to the wound bed, which may prevent infections and decrease need for dressing changes. Thus, it could be a low-cost alternative to hasten healing and improve pain of burn patients. Methods: A phase III randomized controlled trial was conducted from April of 2017 to October of 2018 in Fortaleza, Brazil, and included 115 outpatients aged 18 to 70 years with superficial partial-thickness burns affecting 15 percent or less of body surface area and no previous treatment. Fifty-seven patients were treated with the glycerolized fish skin and 58 with silver sulfadiazine cream 1%. Primary outcomes were reepithelialization time, number of dressings, treatment-related costs, and pain intensity, assessed by means of visual analogue scale, Electronic von Frey, Burns Specific Pain Anxiety Scale, and analgesic use. Patients were evaluated every 48 hours. Results: Patients treated with fish skin required fewer days for reepithelialization (9.7 ± 0.6 days versus 10.2 ± 0.9 days; p = 0.001) and fewer dressings (1.6 ± 0.7 versus 4.9 ± 0.5; p < 0.001). They also had decreased analgesic needs and visual analogue scale, Burns Specific Pain Anxiety Scale, and Electronic von Frey measurements. Finally, fish skin use reduced the final average treatment-related cost per patient by 42.1 percent. Conclusion: By hastening reepithelialization, improving burn-related pain, and decreasing treatment-related costs, Nile tilapia fish skin could benefit the resource-poor public health systems of developing countries. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.